Out-of-school children: Changing landscape of school attendance and barriers to completion - Clarissa C. David; Jose Ramon G. Albert; Jana Flor V. Vizmanos (Philippine Institute for Development Studies (PIDS), 2018)
From 2012 to 2015, the Philippine Institute for Development Studies (PIDS) released a full report, two discussion papers, and two policy notes on Out of School Children (OOSC) in the Philippines. These PIDS papers examined the magnitude of the problem, comparative trends across subgroups of location, sex, and income group of their families, as well as the various possible causes of OOSC. The OOSC statistics from this PIDS-led country study came from national surveys in earlier years, largely the waves of the Annual Poverty Indicator Surveys from 2008 to 2013, as well as from administrative data from the Department of Education, chiefly the 2008-2014 Basic Education Information System. The current study aims to: obtain estimates of out of school (both in magnitude and rates) ; profile OOSC and their families, as well as provide a discussion of the reasons why these children are out of school, and what makes children at risk of dropping out of school; and, discuss and recommend policies to reduce OOSC in the country. The OOSC estimates were generated before the full roll-out of K-12 program that mandates kindergarten, as well as adds two extra years (of senior high school) in basic education. In this context, this current study updates information about OOSC from household surveys and DepED administrative data, partly to assess the degree to which the government has been able to close gaps in education access and completion while at the same time extending its mandate through the K-12 Law. In order to gain a full picture of the problems faced by current OOSC, results of unstructured interviews with parents, school educators, and administrators are also discussed. [...]
Keywords: 330; out of school children (OOSC); gender; poverty; participation rate; OOSC rate; drop-out rate